Microbial Metabolic Capacity for Intestinal Folate Production and Modulation of Host Folate Receptors - Engevik, Melinda A.; Morra, Christina N.; Röth, Daniel; Engevik, Kristen; Spinler, Jennifer K.; Devaraj, Sridevi; Crawford, Sue E.; Estes, Mary K.; Kalkum, Markus; Versalovic, James (Frontiers in Microbiology, 2019)
Microbial metabolites, including B complex vitamins contribute to diverse aspects of human health. Folate, or vitamin B9, refers to a broad category of biomolecules that include pterin, para-aminobenzoic acid (pABA) and glutamate subunits. Folates are required for DNA synthesis and epigenetic regulation. In addition to dietary nutrients, the gut microbiota has been recognized as a source of B complex vitamins, including folate. This study evaluated the predicted folate synthesis capabilities in the genomes of human commensal microbes identified in the Human Microbiome Project and folate production by representative strains of six human intestinal bacterial phyla. Bacterial folate synthesis genes were ubiquitous across 512 gastrointestinal reference genomes with 13% of the genomes containing all genes required for complete de novo folate synthesis. An additional 39% of the genomes had the genetic capacity to synthesize folates in the presence of pABA, an upstream intermediate that can be obtained through diet or from other intestinal microbes. Bacterial folate synthesis was assessed during exponential and stationary phase growth through the evaluation of expression of select folate synthesis genes, quantification of total folate production and analysis of folate polyglutamylation. Increased expression of key folate synthesis genes was apparent in exponential phase, and increased folate polyglutamylation occurred during late stationary phase. Of the folate producers, we focused on the commensal Lactobacillus reuteri to examine host-microbe interactions in relation to folate and examined folate receptors in the physiologically relevant human enteroid model. RNAseq data revealed segment-specific folate receptor distribution. Treatment of human colonoid monolayers with conditioned media from wild-type L. reuteri did not influence the expression of key folate transporters PCFT or RFC. However, conditioned media from L. reuteri containing a site specific inactivation of the folC gene, which prevents the bacteria from synthesizing a polyglutamate tail on folate, significantly upregulated RFC expression. No effects were observed using L. reuteri with a site inactivation of folC2, which results in no folate production. This work sheds light on the contributions of microbial folate to overall folate status and mammalian host metabolism.